2020
DOI: 10.1155/2020/9745206
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Mortality Risk Factors of Acute Ischemic Stroke in Emergency Department in Burkina Faso

Abstract: Objective. To determine the prevalence of ischemic stroke deaths and their predictive factors in the Emergency Department at Yalgado Ouedraogo University Teaching Hospital (YOUTH). Methodology. This was a retrospective study with an analytical and descriptive focus over a period of three years from January 1, 2015, to December 31, 2017. Results. During the study period, 302 acute ischemic stroke patients with a mean age of 62.2±14.26 years were included. Atrial hypertension was the most common vascular risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
0
11
1
2
Order By: Relevance
“…In-hospital pneumonia was indicated to be a predictor of death in patients with acute IS. 14 Contrary to previous research that indicated that elevated tHcy was a useful inflammatory marker that could predict in-hospital pneumonia, 14 our study observed no significant differences in the percentage of inhospital pneumonia between the HHcy and nHcy groups or the percentage of urinary tract infections. THcy has also been considered to be a risk factor for several other diseases, including cardiovascular disease, deep vein thrombosis, pulmonary embolism, and depression, 15 but the findings are not International Journal of Stroke, 18 (3) conclusive.…”
Section: Discussioncontrasting
confidence: 99%
“…In-hospital pneumonia was indicated to be a predictor of death in patients with acute IS. 14 Contrary to previous research that indicated that elevated tHcy was a useful inflammatory marker that could predict in-hospital pneumonia, 14 our study observed no significant differences in the percentage of inhospital pneumonia between the HHcy and nHcy groups or the percentage of urinary tract infections. THcy has also been considered to be a risk factor for several other diseases, including cardiovascular disease, deep vein thrombosis, pulmonary embolism, and depression, 15 but the findings are not International Journal of Stroke, 18 (3) conclusive.…”
Section: Discussioncontrasting
confidence: 99%
“…Sendo assim, os resultados encontrados relacionados a maior prevalência de AVC isquêmico nos casos de pacientes internados com diagnóstico de AVC corroboram com a literatura e com os resultados encontrados em outros estudos nacionais dos autores Sá et al (2014), Lima et al (2015), Silva et al (2018), onde foi verificado uma prevalência de AVC isquêmico de 78,4%; 74,0% e 72,5% respectivamente. Além disto, tal prevalência também foi encontrada em estudos internacionais, como o de Dabilgou et al (2020), com 61% de prevalência no AVC isquêmico. O estudo de Santos e Waters (2020), que se trata de uma revisão integrativa da literatura, também encontrou maior prevalência no AVC isquêmico, onde a incidência variou de 70,4% a 93,9% nos artigos analisados pelos pesquisadores.…”
Section: Resultsunclassified
“…The prevalence of intravenous thrombolysis is low in LMIC compared to HIC, which was 20% [ 43 ]. Intravenous thrombolysis is unavailable in most SSA secondary to cost issues [ 6 , 51 , 52 ]. Although acute IS treatment in the form of intravenous thrombolysis is available in our centre, our cohort's low rate of thrombolysis might be explained by the lack of stroke awareness in the community and the failure to recognise a stroke by health workers and the unavailability of brain imaging in peripheral referral facilities and thus delayed referrals.…”
Section: Discussionmentioning
confidence: 99%